THE ROLE OF SOCIAL MEDIA USER IN MALAYSIA - INDONESIA CULTURAL DISPUTES - Athirah, Azman (Universiti Malaysia Sarawak, (UNIMAS), 2022)
This research on The Role of Social Media User in Malaysia-Indonesia Cultural Dispute is to explore the role of social media users in handling cultural disputes between the two countries. If viewed geographically, it can be known that the two countries are neighbours and are in the same group of regions, namely Southeast Asia. However, Malaysia and Indonesia have conflicts which have occurred in the past, and until now conflicts between the two countries still exist, especially in relation to cultural disputes. The citizens of these two countries often have differences of opinion. The issue is when Malaysia and Indonesia tend to demand and dispute the culture of other countries on social media. When there is such a dispute on social media sites, it will cause a lot of misunderstanding to the community that is users to social media, such as Instagram. As such, this research is conducted to identify the cultural issues that are often disputed between Malaysia and Indonesia, as well as to explore the role of social media users in dealing cultural disputes between Malaysia and Indonesia. The researcher of this study conducted a questionnaire using a qualitative method of open-ended question, whereby, the researcher focused more on the perspective of the targeted respondents from the Instagram social media. Based on this research, researcher has found cultural issues between Malaysia and Indonesia that often arise on social media based on respondents’ perspectives. In fact, researcher have also been able to explore the role that social media users need to play when faced with situations involving intercultural disputes on social media.